The Influence of Work Skills and Work Environment on Employee Performance in Palopo Primary Tax Service Office - Wahdania Amiruddin; Haedar; Indra Kusdarianto (LP2M IAIN Palopo, 2025)
The purpose of this study was to determine the effect of work skills and work environment on the performance of employees at the Palopo Pratama Tax Service Office. The research method used was a quantitative approach. The sampling technique applied was a saturated sampling technique, namely the entire population was used as a sample consisting of 30 respondents. The data analysis technique used was multiple linear regression. The results of this study indicate that 1. Work skills have a positive and significant influence on employee performance. 2. The work environment has a positive and significant influence on employee performance. 3. Simultaneous testing shows that work skills and the work environment simultaneously have an influence on employee performance.